Finite Integral Formulas Involving Multivariable Aleph-Functions. (21st August 2019) - Tadesse, Hagos; Suthar, D. L.; Ayalew, Minilik
Abstract : The integrals evaluated are the products of multivariable Aleph-functions with algebraic functions, Jacobi polynomials, Legendre functions, Bessel-Maitland functions, and general class of polynomials. The main results of our paper are quite general in nature and competent at yielding a very large number of integrals involving polynomials and various special functions occurring in the problem of mathematical analysis and mathematical physics.